Identification of a Novel Small RNA Encoded in the Mouse Urokinase Receptor uPAR Gene (Plaur) and Its Molecular Target Mef2d - Rysenkova, Karina D.; Troyanovskiy, Konstantin E.; Klimovich, Polina S.; Bulyakova, Taisiya R.; Shelomentseva, Ekaterina M.; Shmakova, Anna A.; Tanygina, Daria Yu.; Ivashkina, Olga I.; Anokhin, Konstantin V.; Karagyaur, Maxim N.; Zvereva, Maria I.; Rubina, Kseniya A.; et al. (Frontiers in Molecular Neuroscience, 2022)
Urokinase receptor (uPAR) is a glycosylphosphatidylinositol (GPI)-anchored receptor of urokinase (uPA), which is involved in brain development, nerve regeneration, wound healing and tissue remodelling. We have recently shown that Plaur, which encodes uPAR, is an early response gene in murine brain. Assumingly, diverse functions of Plaur might be attributed to hypothetical, unidentified microRNAs encoded within introns of the Plaur gene. Using a bioinformatic approach we identified novel small RNAs within the Plaur gene and named them Plaur-miR1-3p and Plaur-miR1-5p. We confirmed Plaur-dependent expression of Plaur-miR1-3p and Plaur-miR1-5p in the mouse brain and mouse neuroblastoma Neuro2a cells. Utilizing an in silico MR-microT algorithm in DianaTools we selected two target genes – Mef2d and Emx2 with the highest binding scores to small RNAs selected from identified Plaur-miR1. Furthermore, sequencing of mouse brain samples for Plaur-miR1-5p target genes revealed two more genes – Nrip3 and Snrnp200. The expression of Emx2, Mef2d and Snrnp200 in the mouse brain and Mef2d and Snrnp200 in Neuro2a cells correlated with expression of Plaur and small RNAs – Plaur-miR1-3p and Plaur-miR1-5p. Finally, we demonstrated elevated MEF2D protein expression in the mouse brain after Plaur induction and displayed activating effects of Plaur-miR1-5p on Mef2d expression in Neuro2a cells using Luciferase reporter assay. In conclusion, we have identified Plaur-miR1-3p and Plaur-miR1-5p as novel small RNAs encoded in the Plaur gene. This finding expands the current understanding of Plaur function in brain development and functioning.